Description of two new species of the jumping spider genus Pancorius Simon, 1902 (Araneae: Salticidae) from Southwest China - Wang, Wei-Hang; Wang, Cheng (Zootaxa, 2020)
Two new species of Pancorius Simon, 1902 are diagnosed, described and illustrated from Southwest China: P. candidus sp. nov. (♂♀) from Yunnan Province and P. wesolowskae sp. nov. (♂♀) from Guizhou Province.